Variational calculation of positronium-helium-atom scattering length - Adhikari, Sadhan K. [UNESP] (American Physical Society (APS), 2001)
A basis-set calculation scheme for S-waves Ps-He elastic scattering below the lowest inelastic threshold was formulated using a variational expression for the transition matrix. The scheme was illustrated numerically by calculating the scattering length in the electronic doublet state: a=1.0±0.1 a.u.
Keywords: Atoms; Electrons; Fermions; Green's function; Ground state; Helium; Integration; Matrix algebra; Nonlinear equations; Polynomials; Vectors; Elastic scattering; Legendre polynomials; Positronium; Schrodinger equation; Schwinger variational method; Transition matrix; Wave functions; Zero-energy elastic cross section; Scattering